Analytical model for the frontal impact with a non-deformable barrier. Issue 1 (1st October 2022) - Manea, A M; Iozsa, D; Molea, A; Stan, C
Abstract : According to the literature, a relatively simple models have been developed, capable of simulating the front compartment (FC) integrity during a frontal impact (FI) of a vehicle. These models, known as the Lumped Mass-Spring (LMS), approximates the main subassemblies of the vehicle using a simplified mass-spring system. The paper shows a analytical model for study of the FI behavior of the vehicle with a fixed non-deformable barrier. The principal subassemblies of the FC are approximate with concentrated mass points. These concentrated masses are connected by elastic elements. The generalized coordinates of the displacements of the centers of gravity of the bodies in the longitudinal direction are set. The equations of motion will be obtained based on Lagrange's generalized equations. Initial conditions are required for the model. Solving the system of differential equations is done using the modeling and simulation environment provided by the Matlab Simulink program. Finally, the evolution of the system's deformation, speed and deceleration over time is graphically represented.